Ethnopharmacology Study of Traditional Herbs as Anti-dandruff and Anti-baldness in Amarasi District, Kupang Regency: Studi Etnofarmakologi Ramuan Tradisional Sebagai Antiketombe dan Antikebotakan di Kecamatan Amarasi Kabupaten Kupang - Upa, Muhamad Satria Mandala Pua; Bessi, Marce Inggritha Taku; Korassa, Yulius Baki; I.M. Indrawati, Maria (Universitas Tadulako, 2023)
Backgrounds: Hot weather in Indonesia can cause problems with hair and scalp health, including dandruff (seborrheic) and cause hair roots to become weak, making it easier for hair loss or alopecia to occur. The Amarasi people still do hair and scalp treatments with traditional plants. Objectives: This study aims to determine the ethnopharmacology of herbs as anti-dandruff and anti-baldness in Amarasi sub-district, Kupang district, including plant names, plant properties, plant parts, processing methods, usage methods and usage rules. Methods: This research is a qualitative descriptive study with an exploratory observational design. The data was obtained in the form of a survey by interviewing respondents with the help of a questionnaire. The sample in this study was a traditional healer (Hatra) who understood the use and use of anti-dandruff and anti-baldness drugs. Sampling was carried out using a purposive sampling techniq namely Hatra who were over 20 years old and had experience as a hatred for more than 3 years and above. The sample in this study was 17 traditional healers (Hatra). Results: result research shows that there are 18 plants consisting of 8 single plants and 16 herbs that are used and efficacious as anti-dandruff and anti-baldness. The plant parts used are leaves, fruit, seeds, sap/mucus, tube and oots. the method of processing plants for hair and scalp care by burning, splitting, fryinsqueezing and g, mashing, then, how to use it is washed, smearing, washedmassagingsaged. Rules for using plants 1-2 times a week. Conclusion: The Amarasi community has traditional plants and herbs that can be used as a treatment for scalp problems, including anti-dandruff, preventing hair loss and nourishing hair (anti-baldness). These plants based on research literacy studies conducted by previous researchers proved to have potential in the treatment of anti-dandruff and antibody.